EFFECT OF ECOLOGICAL ENERGY CARRIERS ON FLOW CHARACTERISTICS OF TRACTOR HYDRAULIC PUMP - Ján Kosiba (Journal of Central European Agriculture, 2013)
This paper deals with the effect of ecological energy carrier on flow characteristics of a hydraulic pump. A hydraulic oil MOL Farm UTTO Synt was used as an ecological energy carrier. After completing 900 engine hours, the flow efficiency of the hydraulic pump decreased by Δηpr = 1.197 %. Oil samples were taken from the agricultural tractor Zetor Forterra 114 41. These samples were subjected to an IR spectroscopy analysis in an accredited laboratory WearCheck, Hungary. The following oil properties were examined: kinematic viscosity at 40 °C, viscosity index, silicium and ferrum content.